Umm Kulthum’s Music and Modern Technologies: Musical Heritage and Contemporary Frameworks — What Image, What Music, and What Methodology? - Imed GHDEMSI (Turath, 2025)
This article examines the major transformations in Arab music from cultural and social perspectives, focusing on the case of Umm Kulthum as an exceptional figure who transcended traditional representations of the artist in the Arab world. Her career marked a significant shift—from music conceived merely as entertainment to a symbolic force capable of shaping collective consciousness and redefining aesthetic taste.With the rise of audiovisual and later digital media, the modes of music production and reception have undergone profound change. Digitization has enabled the revival and dissemination of Umm Kulthum’s musical legacy to contemporary audiences, raising questions about the impact of modern technologies on the artistic and aesthetic content of music. This evolution has broadened access to Arab music, moving it from elite spaces to mass consumption arenas shaped by both cultural dynamics and market logic.